Amino Acid and Fatty Acid Compositions of Sea Cucumber Stichopus Vastus from Salemo Island Waters, Indonesia - Abdullah Rasyid (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Coastal waters of Indonesia have considerable biodiversity of sea cucumbers. In the present study the amino acid and fatty acid contents in sea cucumber Stichopus vastus collected from Salemo Island waters Indonesia were determined. Results showed that all essential and non-essential amino acids were found in S. vastus. The major essential amino acid content was arginine (28651.62 mg/Kg). Whereas the major non-essential amino acid content was glycine (60907.24 mg/Kg). The total fatty acids were determined in which finding suggested that saturated fatty acid was more than polyunsaturated fatty acid and monounsaturated fatty acid. The higher saturated fatty acid, polyunsaturated fatty acid and monounsaturated fatty acid were palmitic acid (0.07%), arachidonic acid (0.13%) and palmitoleic acid (0.03%) respectively.